Public Stigma of Stroke Scale: Turkish Validity and Reliability Study - Bahçecioğlu Turan, Gülcan; Özer, Zülfünaz; Yıldız, Esra; Özer, Zülfünaz (Wiley, 2025)
Objective: This study was conducted to examine the validity and reliability of the Turkish version of the Public Stigma of StrokeScale (PSSS).Background: The stigma perceived by patients who have had stroke affects the quality of life as well as many health-related fac-tors. Therefore, it is necessary to determine the society's stigmatization of the stroke patient and to reveal the differences relatedto stroke in different cultures.Design: This study is methodological research.Methods: This study was conducted with 410 individuals aged 18 and over. The data were collected by using descriptive in-formation form and PSSS. The data were evaluated by using exploratory and confirmatory factor analysis, Cronbach's alpha,McDonald's Omega reliability, composite reliability, mean variance extracted and test–retest analysis.Results: Factor load values of the scale items were found to vary between 0.585 and 0.904. The fit index values in the scale werefound as X2 /df = 2.42, < 0.001, CFI = 0.934, TLI = 0.928, SRMR = 0.042 and RMSEA = 0.059. It was found that Cronbach's alphacoefficients of the factors of the scale ranged between 0.916 and 0.946, and the total Cronbach's alpha coefficient was 0.897. TotalMcDonald's omega coefficient was found to be 0.897, and McDonald's omega coefficients of the factors were found to be between0.921 and 0.951. Total composite reliability was found to be 0.981, and total mean variance extracted was found to be 0.740. Itwas found that the Turkish version of the 33-item and four-factor scales was confirmed without any changes in the original scaleform.Conclusion: Turkish version of PSSS is a valid and reliable measurement tool for the evaluation of the stigmatization of strokepatients by the public and for use in clinical practice.
Keywords: Public; Reliability; Stigma; Stroke; Validity